1996
DOI: 10.1177/030098589603300309
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Bluetongue Virus Infection of Ovine and Bovine Endothelial Cells

Abstract: Bluetongue virus (BTV) infection results in disparate clinical syndromes among ruminant species. An in vitro model system of BTV/target cell interaction was developed using umbilical vein endothelial cells (EC)from fetal lambs and calves. These cells had microscopic, ultrastructural, and immunocytochemical features typical of EC. BTV infection in these cells was examined using virus binding assays, plaque assays, a whole-cell enzyme-linked immunosorbent assay, flow cytometry, electron microscopy, and a bioassa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Endothelial cells from different tissue origins within the mammalian host also exhibit differences in BTV or AHSV susceptibility and subsequent immune responses [15,41,42]. This suggests that variations in the susceptibility of vascular endothelial cells within different organs of the infected host could potentially determine tissue tropism and “organ-manifestation” of BTV, particularly the localisation of haemorrhages.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells from different tissue origins within the mammalian host also exhibit differences in BTV or AHSV susceptibility and subsequent immune responses [15,41,42]. This suggests that variations in the susceptibility of vascular endothelial cells within different organs of the infected host could potentially determine tissue tropism and “organ-manifestation” of BTV, particularly the localisation of haemorrhages.…”
Section: Discussionmentioning
confidence: 99%
“…This constituted the first evidence of in vitro IFN production in response to BTV infection. In the following years, BTV was reported to induce IFN in many cell types from various tissues and species including foetal and adult leukocytes and spleen cells from sheep (Rinaldo et al, 1975), endothelial cells from bovine and ovine origin (Coen et al, 1991;Russell et al, 1996;Chauveau et al, 2012) and kidney cells from rabbits, hamsters, monkeys, cats and pigs (Jameson and Grossberg, 1981;Fulton and Pearson, 1982;Taylor and O'Brien, 1985). Importantly, BTV was also shown to induce the production of IFN in multiple human cells with a high efficiency particularly in tumour-derived cell lines (Jameson and Grossberg, 1978, 1979, 1981Joklik, 1981;Chauveau et al, 2012).…”
Section: Btv Induces Type I Ifn Production Both In Vitro and In Vivomentioning
confidence: 99%
“…BTV is a strong inducer of IFN-I both in vivo and in vitro in multiple cell types derived from various tissues and species (26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Recently, we identified RIG-I and MDA5 helicases as sensors of BTV infection in nonhematopoietic cells and showed that these molecules displayed antiviral activities against the virus (26).…”
mentioning
confidence: 99%